Effects of rf power on structural properties of Nc-Si:H thin films deposited by layer-by-layer (LbL) deposition technique - Goh, Boon Tong; Muhamad Rasat Muhamad; Saadah Abdul Rahman (Universiti Kebangsaan Malaysia, 2012)
The effects of rf power on the structural properties of hydrogenated nanocrystalline silicon (nc-Si:H) thin films deposited using layer-by-layer (LbL) deposition technique in a home-built plasma enhanced chemical vapor deposition (PECVD) system were investigated. The properties of the films were characterized by X-ray diffraction (XRD), micro-Raman scattering spectroscopy, high resolution transmission electron microscope (HRTEM) and Fourier transform infrared (FTIR) spectroscopy. The results showed that the films consisted of different size of Si crystallites embedded within an amorphous matrix and the growth of these crystallites was suppressed at higher rf powers. The crystalline volume fraction of the films was optimum at the rf power of 60 W and contained both small and big crystallites with diameters of 3.7 nm and 120 nm, respectively. The hydrogen content increased with increasing rf power and enhanced the structural disorder of the amorphous matrix thus decreasing the crystalline volume fraction of the films. Correlation of crystalline volume fraction, hydrogen content and structure disorder of the films under the effect of rf power is discussed.